Поширення в Україні Botrychium matricariifolium (Ophioglossaceae) - Воткальчук, К.А.; Санісло, Я.П.; Безсмертна, О.О. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2014)
Botrychium matricariifolium (A. Braun ex Döll) W.D.J. Koch —
редкий вид, включенный в «Красную книгу Украины»
(2009). В результате анализа литературных сведений, критического пересмотра гербарных образцов и собственных
полевых исследований авторов установлено, что в Украине
B. matricariifolium найден в 14 локалитетах и встречается в
7 её областях — Волынской, Тернопольской, Винницкой,
Черкасской и Черновецкой (по 1), во Львовской (2) и Закарпатской (7). Приводятся 2 новых местонахождения вида
из Закарпатской обл., установленные по полевым исследованиям авторов, одно из которых является самой большой
популяцией по количеству особей. Botrychium matricariifolium (A. Braun ex Döll) W.D.J. Koch is a
rare species listed in the Red Data Book of Ukraine (2009). An
analysis of the literature data, critical revision of herbarium specimens
and field studies of the authors have shown that in Ukraine
there are 14 records of this species. Botrychium matricariifolium
was found in 7 regions of Ukraine, e.g. Volyn, Ternopil, Vinnytsia,
Cherkasy, and Chernivtsi (1 in each), Lviv (2), and Transcarpathian
(7). Two new localities registered during the field study
in Transcarpathian Region are reported. One of these localities
represents the largest population of the species in Ukraine.